Perencanaan Saluran Sekunder Laliseng Kecamatan Keera Kabupaten Wajo - Rifaldi, Zainal; Yusuf, Andi Rumpang; Syahrir, Suryani (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Irrigation system in paddy fields in Laliseng Village. distribute water to agricultural land by using gravity or allowing water to flow by itself in the field. This is considered ineffective because the channel used is only made simple without careful planning, this causes the water to flow more than the desired debit. And because this simple channel is unable to accommodate rainwater discharge, so that when it rains with high intensity the water can flow to the land instead of the channel it should be.Therefore it is necessary to analyze rainfall and channel discharge, to determine the design of irrigation canals that are in accordance with the planned flood discharge so that irrigation canals can work optimally. In conducting the research, primary data is collected in the form of channel dimensions and secondary data in the form of rainfall data and irrigation maps. The research results obtained trapezoidal channel dimensions with a channel width (b) of 1.4 m and a depth (h) of 0.60 m and accommodates a discharge channel of 1,166 m3/s.